Chemical Looping CH4 Reforming Through Isothermal Two-Step Redox Cycling of SrFeO3 Oxygen Carrier in a Tubular Solar Reactor - Stphane Abanades; Xinhe Wang; Srirat Chuayboon (My University, 2025)
The chemical looping reforming of methane using an SrFeO3 oxygen carrier to produce synthesis gas from solar energy was experimentally investigated and validated. High-temperature solar heat was used to provide the reaction enthalpy, and therefore the methane feedstock was entirely dedicated to producing syngas. The two-step isothermal process encompassed partial perovskite reduction with methane (partial oxidation of CH4) and exothermic oxidation of SrFeO3-δ with CO2 or H2O splitting under the same operating temperature. The oxygen carrier material was shaped in the form of a reticulated porous foam structure for enhancing heat and mass transfer, and it was cycled in a solar-heated tubular reactor under different operating parameters (temperature: 950-1050 °C, methane mole fraction: 5-30%, and type of oxidant gas: H2O vs. CO2). This study aimed to assess the fuel production capacity of the two-step process and to demonstrate the potential of using strontium ferrite perovskite during solar cycling for the first time. The maximum H2 and CO production rates during CH4-induced reduction were 70 and 25 mL/min at 1000 °C and 15% CH4 mole fraction. The increase in both the cycle temperature and the methane mole fraction promoted the reduction step, thereby enhancing syngas yields up to 569 mL/g during reduction at 1000 °C under 30% CH4 (778 mL/g including both cycle steps), and thus outperforming the performance of the benchmark ceria material. In contrast, the oxidation step was not significantly affected by the experimental conditions and the material's redox performance was weakly dependent on the nature of the oxidizing gas. The syngas yield remained above 200 mL/g during the oxidation step either with H2O or CO2. Twelve successive redox cycles with stable patterns in the syngas production yields validated material stability. Combining concentrated solar energy and chemical looping reforming was shown to be a promising and sustainable pathway toward carbon-neutral solar fuels.
Keywords: Chemical-Looping Combustion; Isothermal process; Cycling; Chemical Looping and Thermochemical Processes